Peculiarities of Neurofibromatosis–Noonan Syndrome: Clinical, Radiological, and Histological Characteristics Illustrated - Trimeche, Oumeyma; Hajji, Ekram; Bilel, Ben Amor; Bayar, Ines; Abid, Sana; Marmouch, Hela; Saad, Jamel; Sayedi, Hanene; Hadhri, Rim; Zakhama, Abdelfateh; Khochteli, Ines (Journal of Diabetes and Endocrine Practice, 2025)
Neurofibromatosis–Noonan syndrome (NFNS) is an exceptional disease combining two autosomal dominant conditions: neurofibromatosis type 1 (NF1) and Noonan syndrome. Herein, we report the case of a 37-year-old female patient with a history of Hashimoto thyroiditis who exhibited typical symptoms of pheochromocytoma, which was confirmed with hormonal assessment. On physical examination, she exhibited cutaneous features of NF1. She also had short stature and dysmorphic syndrome consistent with NS. Thus, the diagnosis of NFNS was retained. A cerebral magnetic resonance imaging was carried out, revealing a temporal cavernoma. This case is, to our knowledge, the first report of NFNS with cerebral cavernoma, adding new insight into the clinical spectrum of this rare syndrome. Definitely, gaps remain in our understanding of NFNS, and therefore, other studies are warranted.
Keywords: neurofibromatosis–Noonan syndrome; pheochromocytoma; autoimmune thyroiditis; autoimmune diseases; central nervous system cavernous hemangioma